Controlling the crystallization dynamics of photovoltaic perovskite layers on larger-area coatings - Zeng, Linxiang; Chen, Shi; Forberich, Karen; Brabec, Christoph; Mai, Yaohua; Guo, Fei (Energy and Environmental Science, 2020)
As perovskite solar cells are highly efficient and already meet the efficiency requirement for renewable power generation, more attention is given to technological barriers such as scalability and stability. In particular, the large efficiency losses associated with upscaling lab-scale devices to large-area modules represents one of the major hurdles for commercialization. Given the essential role of the perovskite films in the device performance, it is of critical importance to develop reliable crystallization protocols to deposit high-quality perovskite layers via scalable methods. This review summarizes recent advances in emerging crystallization protocols for the large-scale deposition of perovskite thin films. The unique merits of the well-developed crystallization strategies, including antisolvent, gas quenching, vacuum quenching, etc., are carefully analyzed and discussed. We highlight that, independent of the coating method, creating intermediate phases to decouple the otherwise overlapped solution coating and crystal growth is essential to realize homogeneous coatings of perovskite thin films. Strategies for enhancing the crystal morphology of perovskite films are presented as well, which is vitally important to realize reproducible manufacturing of large-area modules. This tutorial review assists the screening and development of robust crystallization strategies for scalable deposition of high-quality perovskite films for photovoltaic applications.<br